Teacher Assistance in Developing Learning Applications Using Thunkable at Junior High School - Ariansyah, Mochamad Yunus; Dzikrillah, Jordan Amran; Hanin, Jihan Al; Fairuz, Sayida Abqaria; Rosyadah, Sirly Amria; Purnomo, Purnomo (Universitas Muhammadiyah Purworejo, 2025)
Information and communication technology advances have provided many conveniences in education, one of which is in the teaching and learning process. One significant innovation is the development of learning applications that can be accessed by via mobile devices. As an educational institution, SMP Muhammadiyah 2 Kartasura is ready to adopt technology in learning activities which is supported by the availability of technological devices Chromebooks for every student. However, teachers still don't know how to innovate digital-based learning medium because previously they only used conventional learning medium. Therefore, the aim of this service activity is to educate teachers at SMP Muhammadiyah 2 Kartasura about optimizing Thunkable in creating of learning applications. The method used in this service is PAR (participatory action research). The results of this activity show that teachers have high enthusiasm in participating of Thunkable optimization training activities. This can be seen from the strong willing to make Thunkable as well as the active question and answer session between the teacher and the source person. Through this training, teachers can understand the basic concepts of creating learning applications and implement them practically by using the Thunkable platform.